2003
DOI: 10.1002/jobm.200390026
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and exopolysaccharide production in submerged cultures of Pleurotus ostreatoroseusSing. and Pleurotus ostreatus “florida” (Jack.: Fr.) Kummer

Abstract: The species of the genus Pleurotus produce large amounts of biomass and exopolysaccharide (EPS) in submerged cultures, which may be used for biotechnological purposes. In the present work two Brazilian autochthonous strains of edible Pleurotus (P. ostratoroseus Sing. and P. ostreatus "florida") were used. The fungi grown in liquid Potato Dextrose medium (PD) were used as inocula to cultivate those microorganisms in the POL culture medium. After a 9-day incubation, the optimal growth time for biomass production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 11 publications
(6 reference statements)
2
20
0
11
Order By: Relevance
“…These values were similar to those found by Rosado et al [20] for the P. ostreatus, which after 7 days of incubation produced 1.4 g L ¡1 of EPS, when cultivated in a liquid medium with 60 g L ¡1 of glucose; but they were lower than the EPS values (5.8 g of dry weight L ¡1 ) found for P. ostreatoroseus cultivated under the same conditions. The higher EPS result obtained with the sucrose treatment is in agreement with the results of Leifa et al [16] for producing EPS by Agaricus brasiliensis, when comparing sucrose, glucose, fructose and maltose.…”
Section: Production Of P Sajor-caju Ps-2001 Biomass and Exopolysacchsupporting
confidence: 90%
See 2 more Smart Citations
“…These values were similar to those found by Rosado et al [20] for the P. ostreatus, which after 7 days of incubation produced 1.4 g L ¡1 of EPS, when cultivated in a liquid medium with 60 g L ¡1 of glucose; but they were lower than the EPS values (5.8 g of dry weight L ¡1 ) found for P. ostreatoroseus cultivated under the same conditions. The higher EPS result obtained with the sucrose treatment is in agreement with the results of Leifa et al [16] for producing EPS by Agaricus brasiliensis, when comparing sucrose, glucose, fructose and maltose.…”
Section: Production Of P Sajor-caju Ps-2001 Biomass and Exopolysacchsupporting
confidence: 90%
“…With regard to other Pleurotus species, the values for P. sajor-caju biomass obtained in the present study were apparently lower than those obtained by Burns et al [6], who observed values of 9.7 g L ¡1 for P. Xorida, with the diVerence that he used a medium with twice the glucose concentration [20% (w/v)] in a 2-L bioreactor. Rosado et al [20], aiming at the production of P. ostreatus biomass in submerged culture, obtained 22.8 g L ¡1 of dry weight of mycelium after 9 days of incubation, however, in a medium with six times the glucose concentration used in the present work (60 g L ¡1 ).…”
Section: Production Of P Sajor-caju Ps-2001 Biomass and Exopolysacchmentioning
confidence: 96%
See 1 more Smart Citation
“…Although some researchers have reported the effect of liquid media component on the content of EPS from Pleurotus ostreatus (Rosado et al, 2003), Boletus edulis (Deng and Chen, 2005) and Ganoderma lucidum , the optimal carbon and nitrogen sources and environmental conditions of producing EPS from Pleurotus nebrodensis have not been reported. The biomass and content of EPS were observed in liquid media containing five different carbon sources (Table 1).…”
Section: Effects Of Carbon and Nitrogen Sources On Biomass And Eps Comentioning
confidence: 99%
“…Fungus is a large source for finding nematicidal chemicals, and a series of nematicidal substances have been obtained from them (Anke and Sterner, 1997). The genus Pleurotus is one of the most worldwidecommercialised mushroom (Rosado et al, 2003). Several species of the genus were reported to be able to capture and consume nematodes (Thorn and Barron, 1984;Barron and Thorn, 1987).…”
Section: Introductionmentioning
confidence: 99%